Utilization, Predictors and Gaps in the Continuum of Care for Maternal and Newborn Health in Ghana - Juliana Yartey Enos; Richard Dickson Amoako; Innocent Kwao Doku (Global Health and Education Projects, Inc., 2021)
Background: Continuum-of-care (CoC) throughout pregnancy, childbirth and the postnatal period is essential for the health and survival of mothers and their babies. This study assesses the utilization, predictors, and gaps in the continuum of maternal and newborn health (MNH) services in Eastern Ghana. Methods: A retrospective cross-sectional survey was conducted to assess utilization of MNH services and their determinants in the East Akim Municipality of Ghana. Three hundred and ten (310) mothers aged 15-49 years were sampled from 4 communities (3 rural; 1 urban) in the municipality using stratified sampling methodology. Logistic regression models were fitted to determine the likelihood of utilizing skilled birth attendance (SBA) and postnatal care (PNC) after antenatal care (ANC). Results: Sixty-six percent (66%) of mothers surveyed received the full complement of MNH services (ANC, SBA, PNC) for their most-recent birth. While 98% of mothers made at least one ANC visit with 83.5% receiving the World Health Organization-recommended 4+ visits, only 74% accessed SBA indicating a 24% attrition in the CoC from ANC to SBA, and an 8% attrition from SBA to PNC. About 86% of mothers accessed PNC within 42 days postpartum. Distance to health facility, urban residence, and exposure to media information were strong predictors of the full complement of MNH continuumof- care utilization. Conclusion and Global Health Implications: The study found a remarkable utilization of MNH services in East Akim with significant attrition along the continuum-of-care. Efforts to enhance utilization of the MNH continuum-of-care should focus on increasing access to SBA in particular, through equitable distribution of MNH services in hard-to-reach areas and innovative communication approaches for reducing attrition at each level of the continuum-of-care. Evidence from this study can inform strategies for achieving universal access and utilization of the MNH continuum-of-care towards global goals and improved health outcomes in Ghana and other countries. Key words: • Continuum-of-care • Antenatal care • Skilled birth attendance • Postnatal care • Maternal health services • Maternal health • Newborn health • Ghana Copyright © 2021 Enos et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.